A Novel CCM2 Gene Mutation Associated With Cerebral Cavernous Malformation - Yang, Lipeng; Wu, Jian; Zhang, Jing (Frontiers in Neurology, 2020)
Cerebral cavernous malformations (CCMs) are the second most prevalent type of vascular malformation within the central nervous system. CCMs occur in two forms—sporadic and familial—the latter of which has an autosomal dominant mode of inheritance with incomplete penetrance and variable clinical expressivity. There are three genes considered to be associated with CCMs,—CCM1, which codes for KRIT1 protein; CCM2, which codes for MGC4607 protein; and CCM3, which codes for PDCD10 protein. To date, more than 74 gene mutations of CCM2 have been reported, and approximately 45% are deletion mutations. In this article, we disclose a novel CCM2 genetic variant (c.755delC, p.S252fs*40X) identified in a Chinese family to enrich the database of CCM2 genotypes.